A cross‐sectional study of the beliefs and attitudes towards menstruation of Chinese undergraduate males and females in Hong Kong. Issue 23 (December 2013) - Wong, Wing Chi; Li, Mei Kuen; Chan, Wai Ying Veronica; Choi, Yuen Yu; Fong, Chi Hung Sandra; Lam, Ka Wah Kara; Sham, Wun Chi; So, Ping Ping; Wong, Kit; Yeung, Kuen Ha; Yeung, Tsz Yan
Abstract : Aims and objectives: To explore the beliefs and attitudes towards menstruation of Chinese undergraduates in Hong Kong and to compare those of (1) male and female undergraduates with those of (2) undergraduates studying health‐related vs. nonhealth‐related programmes. Background: Menstruation is typically viewed as a forbidden topic or a troublesome experience. These negative beliefs and attitudes result from existing myths and taboos associated with cultural factors and health education levels. Design: A cross‐sectional survey was conducted in all universities in Hong Kong. Undergraduates were invited through convenience sampling to complete a questionnaire assessing their attitudes and beliefs towards menstruation. Methods: A questionnaire on 'beliefs about and attitudes towards menstruation' was adopted. Questionnaires were self‐administered by the respondents. Results: A total of 450 questionnaires were distributed, and a response rate of 96·6% was obtained; 416 completed questionnaires were collected and analysed. Many Chinese undergraduates agreed that menstruation is annoying, causes disability, involves prescription and proscription and is not pleasant. When comparing the beliefs and attitudes towards menstruation of Chinese male undergraduates with those of female undergraduates, females tended to disagree that menstruation should be maintained secret, but tended to agree that it was annoying. When comparing the beliefs and attitudes towards menstruation of Chinese undergraduates studying health‐related programmes with those under nonhealth‐related programmes, the latter group exhibited a higher level of belief in prescription and proscription for menstruation than the former group. Conclusion: Chinese undergraduates in Hong Kong were influenced by the traditional Chinese culture and social environment, resulting in negative attitudes towards menstruation. This study recommends that sex education, especially reproductive health education, be extended to tertiary education. Relevance to clinical practice: This study provides relevant information on planning the content of sex education or reproductive health education for Chinese undergraduates.